Increased expression of epidermal fatty acid binding protein, cofilin, and 14-3-3-[sigma] (stratifin) detected by two-dimensional gel electrophoresis, mass spectrometry and microsequencing of drug-resistant human adenocarcinoma of the pancreas - Sinha-von Jaschke, Pranav; Schadendorf, Dirk (Electrophoresis, 1999)
In order to study possible mechanisms leading to chemoresistance in pancreatic adenocarcinoma we examined the global protein expression of pancreatic cancer cells in vitro. We used a cell culture model derived from the adenocarcinoma of the pancreas (EPP85-181P). A classical multidrug-resistant subline, EPP85-181RDB, selected in presence of daunorubicin, and an atypical multidrug-resistant cell variant, EPP85-181RNOV, selected in presence of mitoxantrone, were analyzed using two-dimensional electrophoresis. After staining and image analysis, spots of interest were isolated using preparative two-dimensional electrophoresis and subjected to mass spectrometry and microsequencing. Three proteins, E-FABP, cofilin, and 14-3-3-σ (stratifin), were overexpressed in chemoresistant cell lines. Cofilin was present in both multidrug in chemoresistant cell lines. Cofilin was present in both multidrug-resistant cell lines. E-FABP and 14-3-3-σ (stratifin) was found to be overexpressed only in the mitoxantrone-selected atypical multidrug-resistant cell line. The possible significance of these findings is discussed.